2013
DOI: 10.1179/1351000213y.0000000047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on plasma paraoxonase1 activity in rugby players: Dependance on training experience

Abstract: We conclude that in rugby players PON1 changes during ME depend on age, body composition, and training experience. The influence of PON1 Q192R polymorphism on PON1 changes at ME remains debatable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
4
15
3
Order By: Relevance
“…Biochemical parameters did not differ between groups either at rest or at ME. These values are very similar to those obtained in our previous studies [ 9 , 10 ]. However, there has been some tendency (but no statistically significant difference) to a higher antioxidant defense (higher FRAP, UA, and TBil) and lower lipid oxidation (lower TBARS), as well as a more favorable lipid profile (lower TChol, LDL-C, and TG and higher HDL-C) in the PA group ( Table 2 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Biochemical parameters did not differ between groups either at rest or at ME. These values are very similar to those obtained in our previous studies [ 9 , 10 ]. However, there has been some tendency (but no statistically significant difference) to a higher antioxidant defense (higher FRAP, UA, and TBil) and lower lipid oxidation (lower TBARS), as well as a more favorable lipid profile (lower TChol, LDL-C, and TG and higher HDL-C) in the PA group ( Table 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…In our study both FRAP and UA continued to rise 2 hours after ME. Similar results on UA changes were described in other studies [ 9 , 10 , 20 ]. Additionally, Yanai and Morimoto (2004) found that the serum urate levels were significantly elevated even 3 weeks after exhaustive training [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In another study, after maximal exercise (ME), an increase in PON1 activities was found; however, no changes in AE activity were found in trained rugby players. PON1 changes during ME were dependent on age, body composition, and training experience as different from the present study, although the influence of PON1P on PON1 changes at ME was uncertain 49) . In the present study, PON1P was not related to the effects of exercise training on AE activity.…”
Section: Correlations Among Variablescontrasting
confidence: 50%
“…Exercise is another major factor that affects PON1 activity. 9 , 12 , 13 Therefore, to protect against CVD, it is important to monitor one's serum PON1 and HDLs-ARE activities as well as cholesterol levels, with the goal of improving these activities through an appropriate exercise program.…”
Section: Introductionmentioning
confidence: 99%